2018
DOI: 10.3390/app8091513
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Lithology Classification Using Dual-Frequency Pol-SAR Data

Abstract: Lithology classification is a crucial step in the prospecting process, and polarimetric synthetic aperture radar (Pol-SAR) imagery has been extensively used for it. However, despite significant improvements in both information content of Pol-SAR imagery and advanced classification approaches, lithology classification using Pol-SAR data may not provide satisfactory classification accuracy due to high similarity of certain classes. In this paper, a novel Pol-SAR lithology classification method based on a stacked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Previous studies utilizing SAR images to discriminate rock units or lithology usually preferred to use full-polarimetric data such as Radarsat-2 [40] or multi-frequency SAR data for example, shuttle imaging radar (SIC) SAR data [41] or together with other source data such as optical data and elevation data [33]. Very few studies employed the dualpolarization Sentinel-1 SAR data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies utilizing SAR images to discriminate rock units or lithology usually preferred to use full-polarimetric data such as Radarsat-2 [40] or multi-frequency SAR data for example, shuttle imaging radar (SIC) SAR data [41] or together with other source data such as optical data and elevation data [33]. Very few studies employed the dualpolarization Sentinel-1 SAR data.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [40] compared two frequencies (L-band and C-band) in polarimetric SAR images for mapping iron-mineralized laterites, and the L-band provided superior results in comparison to C-band. Dual-frequency polarimetric SAR was used together with a deep learning method to successfully classify lithology [41]. Although the advantages of SAR data have been around for a long time for its imaging capability in moist and vegetated regions for geological survey [42], later research has proven that vegetation and topography can still limit the reliability of SAR in geological interpretation [43].…”
Section: Introductionmentioning
confidence: 99%
“…While the X-band (8~12 GHz) might not be commonly used for direct lithology identification in remote sensing applications, it can still contribute to lithology identification efforts by providing valuable information through high-precision topographic data. Sentinel-1 [46], polarimetric SAR (Pol-SAR) [47], and Phased Array type L-band SAR (PALSAR) [45,48] are highly favored for lithological mapping. However, studies have shown that radar data generally has lower spatial resolution compared to optical images, and the acquisition and processing of radar data can be complex [45].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, methods to improve the accuracy of rock-type discrimination based on SAR data focus on (i) improvements in classification algorithms (e.g., improvements in deeplearning algorithms) [15], (ii) using time series to filter features [16], and (iii) using multifrequency or fully polarized data [15,17]. With the development of artificial intelligence, the classification ability of classifiers has gradually improved.…”
Section: Introductionmentioning
confidence: 99%